Chemopreventive effect of a mixture of Chinese Herbs (antitumor B) on chemically induced oral carcinogenesis. Issue 1 (15th November 2011) - Wang, Yian; Yao, Ruisheng; Gao, Song; Wen, Weidong; Du, Yinqiu; Szabo, Eva; Hu, Ming; Lubet, Ronald A.; You, Ming
Abstract In this study, we evaluated chemopreventive efficacy of Antitumor B, a Chinese herbal mixture of six plants (Sophora tonkinensis, Polygonum bistorta, Prunella vulgaris, Sonchus arvensis L., Dictamnus dasycarpus, and Dioscorea bulbifera) on the development of 4‐nitroquinoline‐1‐oxide (4NQO) induced oral squamous cell carcinomas in A/J mice. Antitumor B, delivered through diet, inhibited 4NQO‐induced oral cancer development by 59.19%. The reduction of cell proliferation appears to be associated with efficacy of Antitumor B against 4NQO‐induced oral cancer in A/J mice. The expression of epidermal growth factor receptor (EGFR) and phosphorylated EGFR (Tyr1173) were down‐regulated by Antitumor B. Tissue distribution of Antitumor B was determined using obacunone, matrine, and maackiain as marker chemicals. We found significant amounts of obacunone, matrine, and maackiain in the blood after 1‐wk treatment. The concentrations of these three compounds did not increase further at 18 wk, suggesting that plasma concentrations had reached a steady‐state level at 1 wk. There was no significant body weight loss and there was no other obvious sign of toxicity in Antitumor B‐treated mice. These results suggest that Antitumor B is a promising agent for human oral cancer chemoprevention. © 2011 Wiley Periodicals, Inc.